2019
DOI: 10.1002/hep4.1326
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33/ST2‐Mediated Inflammation Plays a Critical Role in the Pathogenesis and Severity of Type I Autoimmune Hepatitis

Abstract: Interleukin (IL)‐33 was recently described as a new member of the IL‐1 family; members of this family have proinflammatory activity. IL‐33 and its soluble receptor ST2 (sST2) have been implicated in the pathogenesis of autoimmune diseases. This study investigated serum IL‐33 and sST2 in type I autoimmune hepatitis (AIH) and the relationship of these molecules with clinical and pathologic parameters. Subjects included 65 patients with AIH who were diagnosed in our hospital. The control population included 17 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
(98 reference statements)
0
18
0
5
Order By: Relevance
“…Acute-onset AIH accounted for 52% of the cases. Twenty patients (30%) had a severe form of AIH (TB >5.0 mg/dL and/or PT <40%) [ 26 ]; 10 patients (15%) had cirrhosis at diagnosis, and 3 patients (5%) developed cirrhosis. Four patients (6%) developed decompensation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute-onset AIH accounted for 52% of the cases. Twenty patients (30%) had a severe form of AIH (TB >5.0 mg/dL and/or PT <40%) [ 26 ]; 10 patients (15%) had cirrhosis at diagnosis, and 3 patients (5%) developed cirrhosis. Four patients (6%) developed decompensation.…”
Section: Resultsmentioning
confidence: 99%
“…The stages of fibrosis were as follows: F0 (6/61, 9.8%), F1 (9/61, 14.8%), F2 (19/61, 31.1%), F3 (19/61, 31.1%), and F4 (8/61, 13.1%). Regarding therapy, most patients (89%) were treated with prednisolone (PSL), and 15 (23%) were treated with azathioprine in combination with PSL [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then investigated the mechanisms involved in BMDCs maturation in EAH model, which is the recognized animal model of AIH. Accumulating evidence has shown that, in AIH patients and EAH model, the serum levels of LPS, TNF-α and IL-33 were markedly increased compared with that in healthy controls [22][23][24] . To reveal whether those elevated cytokines in AIH patients or EAH model could induce the maturation of BMDCs, im-BMDCs were stimulated in vitro with LPS, TNF-α and IL-33, respectively.…”
Section: Cona Trigger Phenotypic Characteristics Of Bmdcs By Aberrantmentioning
confidence: 97%